2002
DOI: 10.1128/cdli.9.3.693-697.2002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Immunoglobulin G Subclass Profiles Induced by Measles Virus in Vaccinated and Naturally Infected Individuals

Abstract: A total of 258 human sera positive for measles antibodies were divided into four different groups: group 1 contained 54 sera from children after natural measles infection (immunoglobulin M [IgM] positive, early infection phase), group 2 contained 28 sera from children after measles vaccination (IgM positive, early infection phase), group 3 contained 100 sera from healthy adults (natural long-lasting immunity), and group 4 contained 76 sera from healthy children (postvaccinal long-lasting immunity). In the earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 21 publications
(16 reference statements)
1
17
1
Order By: Relevance
“…However, RSV-specific IgG 2 antibodies were described against the G protein and not the F-protein, which was explained by the heavy glycosylation of the G protein [Wagner et al, 1989]. A more recent study showed a transient measles virus-specific IgG 2 antibody response during the acute phase of measles virus infection [Isa et al, 2002], which could not be confirmed by the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…However, RSV-specific IgG 2 antibodies were described against the G protein and not the F-protein, which was explained by the heavy glycosylation of the G protein [Wagner et al, 1989]. A more recent study showed a transient measles virus-specific IgG 2 antibody response during the acute phase of measles virus infection [Isa et al, 2002], which could not be confirmed by the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…Scharf et al [13] showed that the dominant neutralizing IgG subclass for HIV-1 in an experimentally produced HIV-specific immune globulin was IgG3, a subclass known to be extremely sensitive to protease treatment. Although previous work had shown that measles-virus-binding antibodies are primarily IgG1, the subclass profile of the functional (i.e., neutralizing) mnAb response in humans had been unknown [21,22]. The present report is the first to document the measles-virus-neutralizing activity of each IgG subclass, and it demonstrates that IgG1 has the highest specific measles-virus-neutralizing activity, with only a minor additional contribution from IgG3.…”
Section: Discussionmentioning
confidence: 75%
“…Although increased levels of Th2 cytokines such as IL-4 and IL-10 were not observed in response to measles vaccination in infants [11], IFN-g responses may be insufficient to induce a complete deployment of the Th1 response. The isotypes of MV-specific antibodies have been previously studied after immunization and natural infection [32][33][34][35][36]. These studies show that, in general, IgG3 is detected early and associated with decreasing levels over time, whereas levels of IgG1 continue to increase; IgG2 is rarely observed.…”
Section: Discussionmentioning
confidence: 96%